Ghosts of the material world in early childhood education: Furniture matters. (June 2019) - Bone, Jane
This philosophically driven work is intended to trouble the position of the small chair in early childhood settings. It is theoretically driven by an aspect of sociological and cultural theory called hauntology, and by the theories of new feminist materialism. The work of Sara Ahmed influences the direction taken here. An assemblage of personal narratives, memories, works of fiction, history, conversations and media reports, along with the documentation of a performative act, is produced. The methodological approach is intra-active and diffractive. The article argues that the small chair is a contentious and ambiguous artefact, which is taken for granted in early childhood settings, but also problematic when considered from different perspectives – an apparatus that both supports and betrays the body/ies that are in contact with it. Chairs, as objects that furnish human lives, can also haunt those lives and give contradictory messages of power, comfort and suffering. Now and to come, the chair is a trace, a symbol, an instrument of torture and object of desire.